Human Skin Cancer, Potential Biomarkers and Therapeutic Targets - Blumenberg, Miroslav (IntechOpen, 2016)
Skin cancers, basal and squamous cell carcinomas, malignant melanomas, and Merkel cell carcinomas, constitute arguably the most common and increasingly prevalent human neoplasms. Here we discuss the epigenetic changes in DNA and chromatin, which are increasingly associated with melanoma. Several chapters focus on the posttranscriptional modification of the proteins at the melanocyte cell surface, their role in tumorigenesis, and their potential as therapeutic targets. Specifically, extracellular modifications of integrins, glycosylation of cell surface proteins, and changes of cadherins are presented. In a very interesting approach, a potential to target the mitochondria of melanoma cells is investigated. In conclusion, this volume presents various aspects of human skin cancers, components of the large worldwide effort to combat and eradicate this growing health concern.